Mechanical Properties Of Natural Fibre Reinforced Composite By Using Vacuum Assisted Double Bagging Method - Mydin, Syazana Husna Othuman (Universiti Sains Malaysia, 2021)
This is a study of the mechanical properties of natural fibre composites in terms of tensile, compression and flexural manufactured via vacuum assisted double bagging method. Natural fibre composite demands have increased nowadays with its advantages and wide range of applications. The method used to manufacture the composites also plays an essential role in producing a good product. Sadly, studies relating different type of fabrication methods are not diversely done. Thus, this study will give a start up to the fabrication of composite via double bagging method, especially natural fibre composite. In this study, coconut fibre and oil palm fibre are used as the reinforced materials, whereas for the matrix, EpoxAmite 103 with 103 slow harderner is chosen. The fibre volume fraction of the composite laminate is set at constant value, which is 0.4. Based on the ASTM, the total thickness of the laminate should be within 3mm in total. Consequently, for each composite laminate, two fibre plies are rolled by using a rolling machine. The fibre plies are then weighed to calculate the mass of resin needed. The process of fabrication starts with applying resin on the fibre plies by wet hand layup method, followed by double bagging and vacuum process. To ensure the uniform pressure distribution on the laminates, breather is used in between each bagging. This will give a result of laminates with smooth surface and good quality. Since there are three mechanical tests, three batch of double vacuum bagging method is done for each fibre. After the composite is completely cured, each laminate is cut into 5 specimens to be tested for tensile, flexural and compression tests, respectively by using a universal testing machine. Implementation of vacuum assisted double bagging method in this study will gives a better volatile management, lower voids with higher mechanical strength and Young’s modulus of the composite produced. However, the maximum load, stress and strain of the composite produced is lower than the previous studies from researchers. Further improvements are needed on the double vacuum bagging method to give a better result in future research.